2017
DOI: 10.1111/cas.13166
|View full text |Cite
|
Sign up to set email alerts
|

Carfilzomib, lenalidomide and dexamethasone in patients with heavily pretreated multiple myeloma: A phase 1 study in Japan

Abstract: This is the first study in which the carfilzomib, lenalidomide and dexamethasone (KRd) regimen was evaluated in heavily pretreated multiple myeloma. This study is a multicenter, open‐label phase 1 study of KRd in Japanese patients with relapsed or refractory multiple myeloma (RRMM) patients. The objectives were to evaluate the safety, tolerability, efficacy and pharmacokinetics of the regimen. Carfilzomib was administrated intravenously over 10 min on days 1, 2, 8, 9, 15 and 16 of a 28‐day cycle. In cycle 1, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
3
8
0
Order By: Relevance
“…The PK parameters of carfilzomib, C max and AUC last increased in a dose‐dependent manner. These findings are consistent with those of 3 previous studies assessing PK parameters of carfilzomib at different doses in Japanese subjects . Furthermore, the pharmacodynamics analysis revealed that proteasome activities were well inhibited (≥90%) by the carfilzomib administration, which is also consistent with previous Japanese studies …”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The PK parameters of carfilzomib, C max and AUC last increased in a dose‐dependent manner. These findings are consistent with those of 3 previous studies assessing PK parameters of carfilzomib at different doses in Japanese subjects . Furthermore, the pharmacodynamics analysis revealed that proteasome activities were well inhibited (≥90%) by the carfilzomib administration, which is also consistent with previous Japanese studies …”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with those of 3 previous studies assessing PK parameters of carfilzomib at different doses in Japanese subjects. [5][6][7] Furthermore, the pharmacodynamics analysis revealed that proteasome activities were well inhibited (≥90%) by the carfilzomib administration, which is also consistent with previous Japanese studies. 5,6 This study had several limitations: notably, the small sample size, the lack of a comparator and the fact that it enrolled only Japanese patients.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations